Hubungan Efikasi Diri Terhadap Kepatuhan Minum Obat pada Pasien Penyakit Tuberkulosis di Puskesmas Putri Ayu Kota Jambi - Mertisa, Mertisa; Oktarina, Yosi; Subandi, Andi (Jurnal Ilmiah Dikdaya, 2023)
Self-efficacy is a form of individual belief in himself in carrying out an action. Individual confidence is needed by patients undergoing TB treatment to achieve successful self-care. Compliance with taking TB medication is very necessary in completing treatment for 6 months. This study aims to determine the relationship between self-efficacy and medication adherence in tuberculosis patients in Jambi City. This study used a quantitative method and a sectional approach using a total sampling of 48 people. The results of this study showed that 22 tuberculosis patients had high self-efficacy (45.8%) and 26 people (54.2%) had low efficacy. While the level of adherence to taking medication was high for 18 people (37.5%), 18 people (37.5%) had moderate adherence and low adherence was 12 people (25%). The results of the Spearman Rho statistical test obtained a p-value = 0.005 (p <0.05) and r = 0.396, meaning that there is a moderate positive relationship between self-efficacy and adherence to taking medication in tuberculosis patients at the Putri Ayu Health Center, Jambi City. Self-efficacy and medication adherence in tuberculosis patients are still relatively high. Self-efficacy has a low relationship and affects the level of adherence to taking medication in tuberculosis patients. It is hoped that this research can be an evaluation and source of information for the Putri Ayu Health Center, Nursing Education and Profession and further research.